Effect of Ingesting Training Towards Dysphagia in Stroke’ Patients in Haji Hospital and Makassar City Hospital - Afrida Afrida (Faculty of Nursing, Universitas Hasanuddin, 2017)
Introduction: Stroke is a loss of brain function caused by the cessation of blood supply to the brain. One of the most common clinical disorders of stroke is ingesting or dysphagia. This study aims to identify the effect of ingesting exercise to stroke patients with dysphagia in the General Hospital of Haji General Hospital of Makassar City. Method: The design of this study was pre experimental with One Group Pre-Post Test Design. Samples in this study were all stroke patients with dysphagia with Convenience Sampling technique, obtained 20 respondents. Rehabilitation of ingesting exercise is done three times a day at breakfast, lunch, and dinner for seven days in a row. Evaluation of respondents' ingesting status was done on the first day before exercise and last day after practicing exercise. Result: Bivariate results showed that there was an influence between stroke patients with dysphagia and ingesting exercises (p <0.001). Conclusion: It is further recommended that nurses perform structured ingesting exercises as self-care nursing intervention in dealing with stroke patients who have dysphagia.